Container Terminals and Cargo Systems - Kim, Kap Hwan (Springer, 2007)
Ebookcentral.proquest; Since their introduction in the 1960s containers represent the standard unit-load concept for international freight. Container terminals primarily serve as an interface between different modes of transportation, e.g. domestic rail or truck transportation and deep sea maritime transport. Significant gains in productivity can be achieved through advanced terminal layouts, more efficient IT-support and improved logistics control software systems, as well as automated transportation and handling equipment. The primary objective of this book is to reflect these challenges and to present new insights and successful solutions to operational problems of automated container terminals and cargo systems. It comprises reports on the state of the art, applications of quantitative methods, as well as case studies and simulation results. Its contributions are written by leading experts from academia and business and address practitioners and researchers in logistics, transportation, and management.